2015
DOI: 10.1111/pace.12728
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Chronic Valve and Venous Effects of Lumenless versus Stylet-Delivered Pacing Leads in Patients with and Without Congenital Heart

Abstract: The lumenless, 4.1-Fr diameter PL offers improved clinical benefits, better AVV integrity, and venous development compared with larger 5-7-Fr diameter PL and should be considered especially in younger patients with/without CHD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 31 publications
(84 reference statements)
0
11
0
Order By: Relevance
“…Since the maintenance of low thresholds, and associated low generator outputs which extend battery longevity, is paramount when considering pacemaker therapy in the young, this particular site was purposely not utilized. Another favorable aspect of the use of this lead is its improved clinical benefits on the integrity of atrioventricular valves and venous channels, reducing the rate of valvular insufficiency and venous obstruction when compared to the more traditional and larger diameter leads …”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Since the maintenance of low thresholds, and associated low generator outputs which extend battery longevity, is paramount when considering pacemaker therapy in the young, this particular site was purposely not utilized. Another favorable aspect of the use of this lead is its improved clinical benefits on the integrity of atrioventricular valves and venous channels, reducing the rate of valvular insufficiency and venous obstruction when compared to the more traditional and larger diameter leads …”
Section: Discussionmentioning
confidence: 99%
“…Another favorable aspect of the use of this lead is its improved clinical benefits on the integrity of atrioventricular valves and venous channels, reducing the rate of valvular insufficiency and venous obstruction when compared to the more traditional and larger diameter leads. 6 As noted above, although a few studies have been published which report on the short-term performance of the M3830 pacing lead since its approval, the very long-term evaluation is still unknown. This limits the knowledge of chronic efficacy and also any complications that may or may not arise in association with this design, placement, and extraction.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…RVP has been associated with new tricuspid regurgitation and valve abnormalities due to fibrous lesions between the lead and the tricuspid valve in addition to pulmonary hypertension resulting from LV dysfunction . A recent study showed reduced incidence of tricuspid valve abnormalities and venous stenosis with the Medtronic 3830 pacing lead compared to traditional RV pacing leads attributed to the smaller lead diameter (4.1 Fr) . During the entire follow‐up period, there were only two HFHs in our series despite high HBP burden.…”
Section: Discussionmentioning
confidence: 60%